Socio-economic Impact of Academic Staff Union of Universities' Incessant Strikes on Host Communities: Focus on Anyigba Community of Kogi State, Nigeria - Oyebode, Musibau Olabamiji; Obaka, Abel Inabo (NIU Journal of Social Sciences; Vol 8 No 2 (2022): NIU Journal of Social Sciences, Vol. 8 No. 2, June 2022DO - 10.58709/niujss.v8i2.1446, 2022)
Industrial harmony in Nigeria is unstable and unpredictable. At any given time, a union or some unions will embark on industrial actions ranging from lockout, work-to- rule, picketing, protest to strikes. Since 2011, a year hardly passed without the Academic Staff Union of Universities (ASUU) being on strike. Scholars have found and argued that these strike actions have different debilitating consequences. This study examined the impact of ASUU's strike actions on the socio-economic milieu of Anyigba community of Kogi State. The main objective of the study was to ascertain the educational, religious, security, peace and commercial impact of ASUU's strikes, five research questions were drawn: What are the consequences of ASUU's strike actions on religion and morality? In which ways do the strikes pose threat to security? In which ways do the strikes retard the economy of the host community? How do the strikes affect educational advancement? How do the strikes disrupt town and gown relations? The paper was anchored on system theory. Applying survey method of research, a set of questionnaire was administered on 200 respondents. Twenty other members of Anyigba town were also interviewed. Method of data analysis was descriptive statistics presented in themes using Google analyzed participants' responses into pie-charts, histograms and Bar-charts. Findings show that ASUU's strike actions negatively impacted on morality, threatened security and retarded the economy. Based on the findings, the paper recommends government's implementation of agreements, adequate funding and entrenchment of university autonomy. Keywords: industrial harmony, strike, university, community, morality